Avaliação de tratamentos de superfície da cerâmica YTZP sobre a resistência de união a um cimento resinoso - May, Michele Mirian (2015)
This in vitro study was conducted to evaluate the influence of surface treatments on the bond strength between an yttrium-stabilized tetragonal zirconia polycrystal (Y-TZP) ceramic and resin cement. For this purpose, 120 Y-TZP blocks (IPS e.max® ZirCAD in inLab®) were randomly distributed into 12 experimental groups (n = 10), according to six surface treatment strategies and two storage conditions (24 hours post cementation and after 60 days in water and 10,000 thermocicles): AS (as sintered, no treatment); TBS (tribochemical silica coating followed by silanization); AAP (particle abrasion with 50 μm aluminum oxide followed by application of Monobond®Plus); FS (fusion sputtering); SN (5 nm SiO2 nanofilm deposition and silanization) and FSSN (FS + SN). The Y-TZP blocks were embedded in acrylic resin and cylinders of resin cement (Ø=0.96 mm x 1 mm in height) (RelyX ARC) were built up on the ceramic surface. After the storage, the specimens were submitted to microshear test (μSBS) (1 mm/min) in a universal testing machine. After testing, the surfaces were analyzed with a stereomicroscope and scanning electron microscope (SEM) in order to categorize the failure modes. One additional specimen per surface treatment strategy was analyzed by X-ray diffraction, for phases content, and by SEM for micromorphology observation. Bond strength values were statistically analyzed by Kruskal-Wallis and Mann Whitney tests for surface treatments (p <0.001) and aging factor (p <0.05). In both storage conditions, TBS and AAP provided higher bond strength values, followed by FSSN, FS and SN groups. The aging negatively influenced the results, with one exception for the FS. An increase in the amount of monoclinic phase was observed in the abraded groups. Sandblasting of alumina particles followed by application of a primer with MPA is as effective as the tribochemical treatment combined with silane for pretreatment of the Y-TZP surface, with respect to the bond strength to the composite.